American Studies after the Internet. - Klein, Lauren Frederica (American Quarterly, 2012)
The article reviews several books including "The Computer Boys Take Over: Computers, Programmers, and the Politics of Expertise" by Nathan Ensmenger, part of the MIT Series in the History of Computing, "Programmed Visions: Software and Memory" by Wendy Hui Kyong Chun, part of the MIT Series in Software Studies, and "Race After the Internet," edited by Lisa Nakamura and Peter A. Chow-White.